Gorlin-goltz syndrome – case report (Research, Society and Development, 2021)
Introduction: Gorlin-Goltz syndrome is also referred to as basal cell nevus syndrome or basal cell nevoid carcinoma syndrome. This is a rare autosomal dominant inherited disorder caused by mutation in the PTCH1 tumor suppressor gene. Case report: A 15-year-old male patient sought the Maxillofacial Surgery service, reporting mild pain in the right retromolar region, and an orthopantomography was requested, noting the presence 1 maxillary injury and 2 mandible injuries (left and right), all associated with impacted teeth. In the investigation, we found calcification of the cerebral scythe, pontification of the turgical saddle, and depressions in the sole of the feet. Enucleation and curettage of maxillary lesions and removal of impacted teeth were performed. At histopathological examination, Odontogenic Keratocyst was diagnosed. Discussion: SGG is a neurocutaneous disorder that manifests mainly in young patients without gender preference. Kimonis et Al (1997) determine a form of diagnosis by the presence of larger and smaller criteria. In the reported case, three major and one minor criteria were found. It is concluded, therefore, that despite the several diagnostic findings, the most relevant for the maxillofacial surgeon are the keratocysts, which have a high recurrence and destruction power, being present in 70% of the SGG cases. more frequent in the jaw and associated with teeth included. So far, the diagnosis and treatment of the case mentioned has been satisfactory, and a multidisciplinary follow-up is also required.